Impact of the botulinum-A toxin on prevention of adult migraine disorders - Bin Shen, Lan Wang (Journal of Integrative Neuroscience, 2020)
A systematic review of the impact of botulinum-A toxin as a therapeutic regimen for the management of adult migraine disorders is shown to that Botulinum-A toxin provides a more significant reduction in the number of headache episodes per month relative to placebo (MD: -0.61, 95% CI: -1.02 to -0.19). In subgroup analysis, botulinum-A toxin significantly reduced headache episodes per month relative to placebo for chronic migraine (MD: -1.68, 95% CI: -3.31 to -0.06), migraine (MD: -2.43, 95% CI: -4.08 to -0.77), and follow-up time in 16 weeks (MD: -2.19, 95% CI: -3.84 to -0.53). Statistical differences were not found in subgroup analyses of data relating to chronic migraine, episodic migraine, and other treatment course durations. An analysis of chronic and episodic migraine, botulinum-A toxin did not significantly differ from placebo in the proportion of patients achieving a fifty percent reduction in the number of headaches per month. In terms of patients' subjective reporting of headaches, botulinum toxin A conferred significant improvements when assessment questionnaires of migraine disability and migraine impact were analyzed. However, differences were not substantial with data from the 6-item headache impact test. This meta-analysis demonstrated that botulinum-A toxin as a therapeutic regimen improved the impact of chronic migraines after 16 weeks of therapy, although this was not the case for episodic migraine.